2019
DOI: 10.3390/ijms21010295
|View full text |Cite
|
Sign up to set email alerts
|

Granulosa-Lutein Cell Sirtuin Gene Expression Profiles Differ between Normal Donors and Infertile Women

Abstract: Sirtuins are a family of deacetylases that modify structural proteins, metabolic enzymes, and histones to change cellular protein localization and function. In mammals, there are seven sirtuins involved in processes like oxidative stress or metabolic homeostasis associated with aging, degeneration or cancer. We studied gene expression of sirtuins by qRT-PCR in human mural granulosa-lutein cells (hGL) from IVF patients in different infertility diagnostic groups and in oocyte donors (OD; control group). Study 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
(126 reference statements)
0
16
0
Order By: Relevance
“…HDAC4 and HDAC10 are Class II HDACs, which are associated with proliferation, migration, and invasion of a variety of cancers ( Cai et al, 2018 ; Cheng et al, 2021 ). SIRT5 is a Class III HDAC that is involved in oxidative stress or metabolic homeostasis related to aging, degeneration, or cancer ( Gonzalez-Fernandez et al, 2019 ). Relevant studies revealed that SIRT5 can promote autophagy of gastric cancer cells, and SIRT5 can inhibit peroxisome-induced oxidative stress, thus protecting the liver and inhibiting the development of hepatoma cells ( Chen et al, 2018 ; Gu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC4 and HDAC10 are Class II HDACs, which are associated with proliferation, migration, and invasion of a variety of cancers ( Cai et al, 2018 ; Cheng et al, 2021 ). SIRT5 is a Class III HDAC that is involved in oxidative stress or metabolic homeostasis related to aging, degeneration, or cancer ( Gonzalez-Fernandez et al, 2019 ). Relevant studies revealed that SIRT5 can promote autophagy of gastric cancer cells, and SIRT5 can inhibit peroxisome-induced oxidative stress, thus protecting the liver and inhibiting the development of hepatoma cells ( Chen et al, 2018 ; Gu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As feedback, TGF-β signaling antagonizes SIRT7 expression by causing SMAD3/4 to recruit HDAC8 to the SIRT7 promoter and thus chromatin to be remodeled through H4 deacetylation [ 102 , 103 ]. Meanwhile, SIRT7 expression in granulosa-lutein cells from women without ovarian factor was higher with increasing age and was significantly higher in women who responded poorly to in vitro fertilization (IVF) [ 104 ]. Regarding the immune system, SIRT7 silencing reduced lipopolysaccharide (LPS)-induced pro-inflammatory effects and induced an endomesenchymal transition that increased endothelial barrier permeability.…”
Section: Sirt7 Association With Agingmentioning
confidence: 99%
“… 47 , 48 , 49 The presence of all sirtuins has been confirmed in granulosa cells (GCs) and human ovarian granulosa‐like tumor (KGN) cells. 50 …”
Section: Sirt1 and Ovarian Functionmentioning
confidence: 99%